HUBUNGAN BEBAN KERJA DENGAN KINERJA PERAWAT DI INSTALASI RAWAT INAP RUMAH SAKIT HARAPAN BUNDA KOTA BATAM - TrisyaYona Febrina; Zulkarnain Edward; Nurhafizah Nasution (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
The workload is the frequency of activity - average of each - each job within a certain period. Performance(performance) is a result of work achieved in executing tasks - tasks assigned to them based on skills,experience and seriousness as well as time. The performance of nurses is a problem as long as they are notyet aware of the workload that includes the number of patients, the level of dependence of the patient, thetype of activities to be carried out, the average time of nursing actions, assignment system and facilitieswhich he is responsible for properly implemented. The purpose of this study was to see RelationshipBetween Workloads with performance Inpatient Nurse in HarapanBunda Hospital Batam. This type ofresearch is analytic by using "cross-sectional". The population in this study are all nurses in HarapanBundaHospital Batam as 74he sampling technique used was the total population of all nurses in the inpatient unitHarapanBunda Hospital Batam many as 74 people. Data collected through interviews guided by using aquestionnaire and chech list which is then processed by a computerized system and are presented in tabularform distribution and cross table. The result is that the poor performance of nurses as much as 29.3% and17.4% higher workloads There is significant correlation between workload with the performance of nurseswith a p-value 0.027. To further improve the performance of nurses will have to reassess the balancebetween workload, the number of patients and the number of nurses